Decoding Diversity: Indonesian Student’ Reception of Religious and Multicultural Themes in ‘Mentega Terbang’ Using Stuart Hall’s Encoding/Decoding Framework - Annisa, Firly; Nurnisya, Frizki Yulianti; Sofian, Muhammad Raqib Bin Mohd; Pradipta, Elita Putri; Soliman, Eman M. (Universitas Ahmad Dahlan, 2025)
This research explores the reception of the Malaysian film